Metodologias ativas e sequência didática como ferramenta no processo de aprendizagem de eletromagnetismo - Silva, Frederico Rozendo da (2025)
The technological, social, and economic transformations of recent decades have imposed new challenges on Basic Education, particularly on Science and Physics teaching. Faced with this scenario, it becomes necessary to adopt approaches that foster competencies such as critical thinking, problem-solving, collaboration, and intellectual autonomy. This thesis investigated the impacts of a didactic sequence based on the Theory of Meaningful Learning (TML), integrating Problem-Based Learning (PBL), Maker Culture, and the 6Cs methodology in Electromagnetism teaching on High School. The research adopted a single-group quasiexperimental design, conducted with four classes of 3rd year (12th grade) from a full-time public school in Ceará. The intervention included a pre-test, a post-test, and a satisfaction questionnaire, structured around the integrative theoretical model SIGMA, which articulates cognitive, procedural, and affective dimensions of the teaching-learning process. The final sample consisted of 73 students who fully participated in all three evaluation stages. The quantitative results revealed statistically significant conceptual gains. The normality analysis, conducted using the Shapiro-Wilk test, indicated the absence of a normal distribution in the data (p < 0.05). Therefore, the non-parametric Wilcoxon test was chosen, which confirmed the statistical significance (W = 1431; p < 0.0001) with a moderate effect size (r = 0.33). Qualitative analysis showed high levels of student engagement, especially in the expansion of conceptual understanding, appreciation of experimental practices, stimulation of creativity, and strengthening of collaborative work. It is concluded that the adopted approach promoted the students9 cognition, attitudinal, and social development, confirming the pedagogical potential of active methodologies when applied in a contextualized and reflective manner, and according to the reality of public schools. The research provides theoretical and methodological contributions for the redesign of Physics teaching practices in High School.